The Impact of Resident Involvement on Postoperative Complications following Knee Arthroscopy. Issue 7 (31st July 2020) - Gulbrandsen, Trevor; Shamrock, Alan; Duchman, Kyle; Wolf, Brian; Westermann, Robert; Khazi, Zain
Objectives: Exposure to arthroscopic procedures is essential in orthopedic resident training. Previous studies have demonstrated that resident involvement is not associated with increased risk of short-term complication for various general surgical cases and orthopedic surgeries such as lumbar fusion, hand surgery, and foot and ankle surgery. However, the impact of resident involvement on postoperative complications and operative time following knee arthroscopy, the most common resident case logged orthopedic procedure, is unknown. The purpose of the current study was to investigate whether resident involvement in knee arthroscopic procedures impacts postoperative complication rates and operative time. Methods: The American College of Surgeons National Surgical Quality Improvement Program (NSQIP) registry was queried to identify patients who underwent common knee arthroscopy procedures between 2005 through 2012. Patients with a history of knee arthroplasty, treatment for septic arthritis or osteomyelitis of the knee, or concomitant open or mini-open procedures were excluded from the study. Cases without information on resident involvement were also excluded. A 1:1 propensity score match was utilized based on age, sex, body mass index (BMI), obesity, smoking history, and American Society of Anesthesiologist (ASA) classification to match cases with resident involvement to attending only cases. Fisher's exact test, Pearson's Chi-square tests, and student t-tests were utilized to compare patient demographics, comorbidities, and 30-day postoperative complications. Poisson regression analysis were used to compare operative time between the two groups, with statistically significance defined as P<0.05. Results: Overall, 15, 536 patients that underwent knee arthroscopy were identified, of which 32.8% (n=5092) were excluded due to missing information on resident involvement, concomitant open or mini-open procedures, or treatment of septic arthritis or osteomyelitis of the knee. After propensity score matching, 2, 954 cases (50% with resident involvement) were included in the study. Both groups were similar in age (P=0.987), sex (P=0.970), BMI (P=0.696), diabetes mellitus (P=0.613), chronic obstructive pulmonary disease (P=1.00), smoking history (P=1.00), and ASA classification (P=0.606) confirmed an appropriate match. The overall rate of 30-day complications was similar in the attending only (1.31%) group compared to the resident (1.11%) group (P=0.610; Table 1). There was no significant difference in postoperative surgical complications including superficial wound infection (P=1.00), deep wound infection (P=0.625), wound dehiscence (P=0.250), neurological deficit (P=1.00), or blood transfusion (P=0.375). Furthermore, there was no significant difference in postoperative medical complications including pulmonary embolism (P=0.500), deep vein thrombosis (P=0.616), urinary tract infection (P=1.00), or sepsis (P=1.00). Knee arthroscopy cases with resident involvement had significantly longer operative time (69.6 minutes vs 60.9 minutes, P<0.0001) when compared to cases performed without a resident. Conclusion: Resident involvement in knee arthroscopy procedures is not a significant risk for medical or surgical 30-day postoperative complications. Resident participation in knee arthroscopy cases did increase operative time. This information is valuable for resident education and patient reassurance. Table 1. Comparison of 30-day Complication Rates Between Attending Only and Resident Groups Complications Attending (n=1447) Resident (n=1447) P-Value Overall Complication Rate 19 (1.31) 16 (1.11) 0.61 Superficial Surgical Site Infection 4 (0.28) 3 (0.21) 1 Deep Surgical Site Infection 3 (0.21) 1 (0.07) 0.625 Wound Dehiscence 0 (0) 3 (0.21) 0.25 Urinary Tract Infection 1 (0.07) 2 (0.14) 1 Sepsis 0 (0) 1 (0.07) 1 Neurologic Deficit 1 (0.07) 0 (0) 1 Blood Transfusion 1 (0.07) 4 (0.28) 0.375 Deep Vein Thrombosis 9 (0.62) 7 (0.48) 0.616 Pulmonary Embolism 0 (0) 2 (0.14) 0.5 Operative Time (min)^ 60.89± 48.7 69.57± 53.14 <0.0001* *Significant findings (P<0.05); ^Poisson regression analysis.